Genetic mapping of susceptibility loci in the genes involved in rheumatoid arthritis. - Hardwick, L; Walsh, S; Butcher, S; Nicod, A; Shatford, J; Bell, J; Lathrop, M; Wordsworth, B (1997)
Eighty-nine multicase rheumatoid arthritis families, each containing at least one affected sib pair, have been studied for evidence of genetic linkage to a panel of 315 microsatellite DNA markers. The families were located through the UK national data repository of the Arthritis and Rheumatism Council. Microsatellites were genotyped by semiautomated technology using Applied Biosystems sequencers (ABI 373). Using the SIBPAIR statistical package, linkage to HLA was confirmed (p < 0.0003). Several possible linkages outside HLA were noted, including at least one (p < 0.004) that merits further investigation.